"This Is How We Travel": Sex, Love, Intimacy and the Border. Issue 2 (3rd March 2021) - Daigle, Megan
ABSTRACT: "Movements back and forth […] between cities, between continents, and across oceans and rivers have made travellers of us all, " posits Ruth Behar, "even Cubans who only dream of going places." In Cuba since the dawn of the twenty-first century, socio-economic change is rapid, continuous, and uncertain, but one constant is the near-absolute spectre of the border. The idea of intimate liaisons with foreigners as a kind of "travel" serves as a jumping-off point in this article, where the stories of locals and foreigners who pursue romance, love, and sex across borders of all kinds serve to make visible the connections between the intimate and the international. The Cuban setting makes everyday emotional, affective, and sexual practices – and the body itself – a particularly fertile ground for resistance, as well as a lightning rod for disciplinary action, with the potential to enact or disrupt structures of the border through the mechanisms of sex and body – and of pleasure. Through an exploration of pleasure as powerful and political, the intimate – often sidelined as a "feminine" and apolitical sphere – can be revealed as a productive and radically relational mode, a vector of international and transnational relations, and a fertile ground for resistance. As bordering practices assert themselves in multiple and evolving ways both externally (travel restrictions) and internally (social and economic divisions between Cubans and foreigners), this article explores how bodies become a means of circumventing and reinscribing those same geopolitical, ideological, and sexual borders policed by states.